Effects of tillage method on the carbon footprint, energy budget, and net ecosystem economic efficiency of rice fields - Cheng, Shuang; Xing, Zhipeng; Tian, Chao; Liu, Mengzhu; Feng, Yuan; Zhang, Hongcheng (Frontiers in Sustainable Food Systems, 2023)
Biaxial rotary tillage is considered an effective approach for enhancing the structure of soil in rice fields. There are few reports on the effects of biaxial rotary tillage on the carbon footprint (CF), energy budget, and net ecosystem economic efficiency (NEEB) of rice fields. Here, we evaluated the effects of dryland biaxial rotary tillage (DBRT), as well as two traditional tillage methods, dryland and paddy field in uniaxial rotary tillage (DPURT) and paddy field in uniaxial rotary tillage (PURT), on the CF, energy budget, and NEEB of rice production to clarify the economic and ecological utility of DBRT. The tillage depth was 9.5–15.4% higher under DBRT than under DPURT and PURT (p < 0.05). The soil bulk density was 5.4–12.1% lower under DBRT than under DPURT and PURT. The rice grain yield was 7.6–8.7% and 17.7–19.1% higher under DBRT than under DPURT and PURT, respectively (p < 0.05). The total global warming potential was 7.6–10.6% and 17.0–20.4% lower under DBRT than under DPURT and PURT, respectively (p < 0.05). The CF was 17.7–18.9% and 35.4–36.1% lower under DBRT than under DPURT and PURT, respectively. The energy use efficiency was 8.7–10.4% and 16.4–18.3% higher under DBRT than under DPURT and PURT, respectively. The NEEB were 13.2–15.7% and 28.6–32.1% higher under DBRT than under DPURT and PURT, respectively. In summary, DBRT is beneficial for increasing rice yield and reducing greenhouse gas emissions, thereby improving the economic and ecological benefits of rice.